The Impact of Health Capital on Economic Growth in the Balkan Countries (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
This study estimates the impact of health capital on economic growth in 10 Balkan countries over the 2000-2019 period. We used panel autoregressive distributed lag (ARDL) of a pooled mean group (PMG) to examine this relationship. Our results revealed that economic growth responds to short-term and long-term health capital changes. Estimation results indicate a positive relationship between health capital and the economic growth of Balkan countries. According to the results, increased health expenditure stimulates higher economic growth and development. The findings imply the need to formulate policies that assign higher priority to the healthcare sector, which would help sustain future economic growth in Balkan countries.